Evaluation of the health effects of a neighbourhood traffic calming scheme. Issue 10 (13th September 2004) - Morrison, David S; Thomson, Hilary; Petticrew, Mark
Abstract : Study objective: To assess the secondary health impacts of a traffic calming scheme on a community. Methods: Prospective cohort study of a randomly selected sample of the local community using postal questionnaires and pedestrian counts on the affected road six months before and six months after the implementation of the scheme. The setting was a community in which a traffic calming scheme was built in the main road (2587 households). The Short Form 36 version 2 was included in the questionnaire and summary measures of physical health (physical component summary) and mental health (mental component summary) calculated. A random sample of 750 households was initially posted the pre-intervention questionnaire. Main results: There were increases in observed pedestrian activity in the area after the introduction of the traffic calming scheme. Physical health improved significantly but mental health did not change. Traffic related problems improved, while other local nuisances were reported to be worse. Conclusions: The introduction of a traffic calming scheme is associated with improvements in health and health related behaviours. It is feasible to prospectively evaluate broader health impacts of similar transport interventions although poor response rates may limit the validity of results.